Analisis Ketahanan Pangan Rumah Tangga Peternak Domba Kasus pada Rumah Tangga Peternak Domba di Kecamatan Kertajati Kabupaten Majalengka, Jawa Barat - Kuswaryan, Sondi; Fitriani, Anita; Daud, Andre Rivianda; Firmansyah, Cecep; Rahmah, Ulfa Indah Laela (Universitas Galuh, 2025)
In rural West Java, sheep are a mainstay livestock commodity to support livelihoods, because they function dually as a source of food and a source of income, and play a role in maintaining household food security. The research was carried out in Kertajati District, Majalengka Regency, aiming to analyze the food security status of sheep farmer households, and the variables that influence it. The survey method was used to collect respondents data from 126 households. Food consumption status and household food security were identified by interviews using the 3 x 24-hour food recall method. Variables that influence food security status are identified using a binary logistic regression model. The research results show that 37.30 percent of sheep farming households are food secure, 27.78 percent are food vulnerable, 23.81 percent are food questionable and 11.11 percent are food insecure. Sheep farming contributes 30.35 percent to total household income and can provide 65.24 percent of the budget to meet food needs. The number of sheep owned and the number of members in the farmer's household have a significant effect (p < 0.01) on food security status. The existence of sheep farming plays a very important role in maintaining sustainable household food security. To reduce the negative impact of the deagrarianization process on household livelihoods, sheep farming must be strengthened, among other things, for sheep farming whose semi-intensive patterns are suitable for being transformed into intensive rearing patterns, accompanied by the introduction of feed technology for more efficient feed provision and feeding.